Environmental impacts of urbanisation on forest reserved areas in Hulu Langat - Asmawi, M. Zainora; Ibrahim, Ainaa Nawwarah (2011)
Generally, forests are known to have a wider range of socio-cultural, economic and environmental values. Forests have important roles to play in sustaining many aspects of human dimensions. For instance, these include the use of forests as resources for education and recreation purposes, and also the role of forests in conservation of biological diversity as well as in maintaining global climate. In the latter, there has been much debate and even controversial views, although it is now accepted that forests are important as sinks and sources of carbon dioxide (CO2), which is important in combating global warming. More recently, urbanisation has been identified as environmental stressors (Nowak and Walton, 2005; Shortle J.S., et al. 2005). According to Jamaluddin Md. Jahi (2009) and Hirchman (2003), the exploitation of natural resources and other improperly planned and inadequately controlled development activities often lead to environmental degradation.